BUDAYA KONSUMERISME DALAM IKLAN SHOPEE VERSI CETAR MEMBAHANA - Heri Davidson; Dian Novitasari (SEMIOTIKA: Jurnal Komunikasi, 2022)
The culture of consumerism forms a social space in which consumers are designed to live socially so that they follow the flow of signs, meanings, images and identities that flow endlessly.Â  In this situation, consumer lifestyles are more towards consumptive lifestyles, which are never satisfied with something they already have.The theory used in this research is the theory of Roland Barthes's semiotics.Â  In this research, the researcher will focus on the "sign" as the object of study, and interpret and understand the code behind the sign in the Shopee ad version "shaking shakes" as an object of research that has an ideology of consumerism in it.The research method by the author is a qualitative research method, the qualitative approach is more descriptive in nature and the data collected in the form of words or images so that it does not emphasize the calculation of numbers and focus the meaning of social and cultural phenomena.The results showed that in the shopee advertisement the â€œshaking shakesâ€ version after being analyzed with a Roland Barthes analysis knife turned out to contain an ideology of consumerism. The based on the result of the analysis in this study also found that the myth of shopping is considered there is, goods worn by someone can increase prestige, and shopping at shopee can solve problems, especially appearance problems.